Postcolonial Witnessing - Craps, Stef. author. aut Link
XI, 181 p.
Keywords: Postcolonial Witnessing argues that the suffering engendered by colonialism needs to be acknowledged more fully, on its own terms, in its own terms, and in relation to traumatic First World histories if trauma theory is to have any hope of redeeming its promise of cross-cultural ethical engagement.